2018
DOI: 10.1088/1612-202x/aaa9c7
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control of different generation regimes in mode-locked all-fibre F8 laser

Abstract: We demonstrate for the first time an electronically controlled realisation of markedly different generation regimes in a mode-locked all-fibre figure-eight (F8) Yb-doped laser. Electronic adjustment of the ratio of pumping powers of two amplification stages in a nonlinear amplifying loop mirror enables the establishment of stable pulse generation regimes with different degrees of coherence and control over their parameters within relatively broad limits, with the pulse duration range exceeding a factor of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…This laser layout combines the reliability and robustness of conventional F8 lasers with the flexibility of NPE-based lasers, providing access to a variety of generation regimes with a relatively wide adjustment range of the main pulse parameters. Moreover, it enables reliable and reproducible live electronic adjustment of the lasing regimes [12], which is practically impossible to do by adjusting fibre-based polarisation controllers in NPE-based lasers. Indeed, as in this laser configuration the generation properties are practically independent of the ambient conditions, it is only necessary to determine once, initially, the required values of the ratio of the pump powers and the ranges of their adjustment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This laser layout combines the reliability and robustness of conventional F8 lasers with the flexibility of NPE-based lasers, providing access to a variety of generation regimes with a relatively wide adjustment range of the main pulse parameters. Moreover, it enables reliable and reproducible live electronic adjustment of the lasing regimes [12], which is practically impossible to do by adjusting fibre-based polarisation controllers in NPE-based lasers. Indeed, as in this laser configuration the generation properties are practically independent of the ambient conditions, it is only necessary to determine once, initially, the required values of the ratio of the pump powers and the ranges of their adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we use a regression model based on a NN algorithm for an automated exploration of the cavity parameter space and a rapid identification of modelocked solutions. It is worth noting that the electronic control over the parameters of the generated pulses that is afforded by the NALM laser architecture is exempt from a complicated computer search of suitable regimes during laser operation [12]. Correspondingly, here we use the NN only to quickly figure out the output pulse features that are attainable through variation of the adjustable system parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrate special 8-figure mode-locked laser for generation double-scale pulses with variable degree of coherene. Previously, we showed that adding additional amplifying spans of fibre inside laser cavity leads to generation of pulsed regimes with different time duration, energy, optical spectrum and coherence degree 3 . Enormous number of possible pulse regimes allows tuning pulse parameters almost continuously and opens a way for proposed researches.…”
Section: Introductionmentioning
confidence: 99%
“…One of the important developments of NALM technology was addition of a second independently pumped active medium into the laser cavity with NALM. Introduction of a second active medium directly into the NALM loop [3,4] gave rise to the NALM2 technology, whereas a second active medium added to the initially passive loop of an F8 fibre laser [5,6] transformed its cavity into а double NALM (we will henceforward term it D-NALM). The location of specific elements along the fibre laser cavity [7] and its general topology affect the laser generation properties.…”
Section: Introductionmentioning
confidence: 99%